Autism and attachment disorders – how do we tell the difference?. (November 2022) - Davidson, Claire; Moran, Heather; Minnis, Helen
SUMMARY: Clinicians assessing children with autism are sometimes faced with a dilemma, especially if there is a definite or suspected history of abuse or neglect: is this autism or attachment disorder? This is important because the attachment disorders (reactive attachment disorder and disinhibited social engagement disorder) are thought to be caused by abuse or neglect, whereas autism is not. We discuss the Coventry Grid, a clinical tool aiming to aid differentiation between autism and attachment disorders. We examine the small body of empirical studies focusing on this differential diagnosis and find that the Coventry Grid can be regarded as an evidence-based tool. We also discuss preliminary findings regarding a relatively unstructured observational method involving two assessors who engage the child in jokes and playful social dilemmas, which might help clinicians elicit the information required to complete the Coventry Grid.